2022
DOI: 10.14740/wjon1536
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Interleukin-6 Levels and Lymph Node Metastasis in Bladder Cancer Patients

Abstract: Background: Bladder cancer (BC) is one of the urological cancers with high prevalence, mortality, morbidity, and expenditure rates. Urothelial malignancies account for about 90% cases of BC, with squamous and adenocarcinomas making up the remaining 10%. Lymph node metastasis (LNM), the most common type of BC metastasis, is generally found in the pelvic lymph nodes. LNM significantly affects the chances of survival and prognosis for patients with BC. It is feasible to stratify and assess the malignancy of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Inflammatory markers are indicators of inflammation but can also be an indicator of distant metastases. Warli et al detected that higher level of Il-6 correlated with metastases in lymph nodes in bladder cancer [ 53 ]. On the other hand, Hashemzehi et al observed an association of Il-6 -174G>C polymorphism with the risk of ovarian and also cervical cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers are indicators of inflammation but can also be an indicator of distant metastases. Warli et al detected that higher level of Il-6 correlated with metastases in lymph nodes in bladder cancer [ 53 ]. On the other hand, Hashemzehi et al observed an association of Il-6 -174G>C polymorphism with the risk of ovarian and also cervical cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%